Evolution, diversification, and biogeography of grasshoppers (Orthoptera: Acrididae) - Song, Hojun (2018)
The grasshopper family Acrididae is one of the most diverse lineages within Orthoptera, including more than 6,700 valid species distributed worldwide. Grasshoppers are dominant herbivores and represent a ubiquitous component of grasslands around the world. They have also diversified into desert, semi-aquatic, alpine, and tropical forest habitats, and exhibit a wide array of morphological, ecological, and behavioral diversity. Despite their diversity and our familiarity with grasshoppers, there has not been a comprehensive phylogenetic hypothesis for the Acrididae. In this study, we propose the first comprehensive phylogeny of Acrididae based on the mitochondrial genomes and nuclear genes to test monophyly of the family and different subfamilies as well as to understand the evolutionary relationships among these groups. We recovered the family as a monophyletic group and inferred that the common ancestor of modern grasshoppers originated in South America based on a biogeographic analysis. Within Acrididae, we recovered four major clades as well as several well-characterized subfamilies, but we also found that paraphyly is rampant across many subfamilies, highlighting the need for a taxonomic revision of the family. The divergence time estimate analysis suggested that Acrididae originated in the Paleocene of the Cenozoic period (59.3 MYA) and the diversification of the family can be characterized as a series of founder events with subsequent radiation. Because the separation of South America and Africa predated the origin of the family, we hypothesize that the current cosmopolitan distribution of Acrididae is largely achieved by dispersal. We estimate that there have been a number of colonization and recolonization events between the New World and the Old World throughout the diversification of Acrididae, and thus the current diversity in any given region is a reflection of this complex history.